Effects of a common variant in the CD38 gene on social processing in an oxytocin challenge study: possible links to autism - Sauer, Carina; Montag, Christian; Kirsch, Peter; Reuter, Martin (Neuropsychopharmacology, 2012)
The intranasal application of oxytocin (OT) has been shown to influence behavioral and neural correlates of social processing. These effects are probably mediated by genetic variations within the OT system. One potential candidate could be the CD38 gene, which codes for a transmembrane protein engaged in OT secretion processes. A common variation in this gene (rs3796863) was recently found to be associated with autism spectrum disorders (ASD). Using an imaging genetics approach, we studied differential effects of an intranasal OT application on neural processing of social stimuli in 55 healthy young men depending on their CD38 gene variant in a double-blind placebo-controlled crossover design. Genotype had a significant influence on both behavioral and neuronal measures of social processing. Homozygotic risk allele carriers showed slower reaction times (RT) and higher activation of left fusiform gyrus during visual processing of social stimuli. Under OT activation differences between genotypes were more evident (though not statistically significantly increased) and RT were accelerated in homozygotic risk allele carriers. According to our data, rs3796863 mainly influences fusiform gyrus activation, an area which has been widely discussed in ASD research. OT seems to modulate this effect by enhancing activation differences between allele groups, which suggests an interaction between genetic makeup and OT availability on fusiform gyrus activation. These results support recent approaches to apply OT as a pharmacological treatment of ASD symptoms.
Gesehen am 30.04.2018